Platelet Coagulant Activities and Retinal Vein Thrombosis - Walsh, Peter N.; Goldberg, Richard E.; Tax, Richard L.; Magargal, Larry E. (Thrombosis and Haemostasis, 1977)
To determine whether platelets play a role in the pathogenesis of retinal vein occlusion (RVO), platelets and coagulation were evaluated in 28 patients with RVO. Platelet coagulant activities concerned with the initiation and early stages of intrinsic coagulation were 2–4 fold increased in 9 patients with acute primary RVO but not in patients with acute secondary (10 patients) or chronic (9 patients) RVO. Platelet factor 3 activity, platelet aggregation, serotonin release by platelets and plasma coagulation were normal in all patients. Platelets may provide a trigger mechanism for venous thrombosis in the eye when local conditions permit.